Reanalyzing a Randomized Controlled Trial of Invasive Aspergillosis Using a Desirability of Outcome Ranking Approach: Voriconazole Versus Amphotericin B Deoxycholate - Julio C Zuniga-Moya; Marcela Araujo de Oliveira Santana; Luis Ostrosky-Zeichner; George R Thompson; Thomas J Walsh; Andrej Spec (Clinical Infectious Diseases, 2026)
Abstract Efficacy of antifungal therapy in invasive aspergillosis relies primarily on mortality, overlooking critical measures of treatment response. We used the Mycoses Study Group Education & Research Consortium (MSG) Desirability of Outcome Ranking (DOOR) framework to assess efficacy of antifungal therapies by integrating mortality, treatment failure, and severe adverse events. Voriconazole achieved better overall outcomes than amphotericin B using the DOOR approach.